(untitled) (Religion, Culture, and State Journal, 2021)
Throughout the history of combating terrorism in Indonesia, the Indonesian National Armed Forces (Tentara Nasional Indonesia - abbreviated as TNI) has played an important role in combating terrorist acts. The role and involvement of the TNI in general has been regulated in statutory regulations. Act 5 of 2018 states that the TNI has a duty to combat terrorism, this effort is called military operations other than war. This military involvement will be represented by the TNI Joint Special Operations Command. However, the involvement of the TNI in combating terrorism in Indonesia can also lead to a number of negative implications, such as the occurrence of human rights violations. If the TNI commits human rights violations while arresting suspected terrorists, the public will find it difficult to hold them accountable and monitor the course of the case. Past experience illustrates that there have been many cases of violations of human rights violations committed by the TNI and there is no legal process. Therefore, in order to avoid the occurrence of human rights violations, it is important to formulate the intensity and situations in which the TNI can be involved in combating terrorism. Thus, there are at least three things that are studied in depth in this study. First, analyze the regulations on combating terrorism in Indonesia. Second, analyze potential human rights violations by the TNI in combating terrorism. Third, formulate a counterterrorism design for the TNI to prevent human rights violations.